2010
DOI: 10.9755/ejfa.v22i4.4876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arsenic and manganese on root growth and cell division in root tip cells of green gram (Vigna radiate L.)

Abstract: Heavy metals are the metals having a density at least five times more than that of water. They are normally regarded as ones having an atomic number of 22-92.The effects of different concentration (5, 10, 25, 50 and 100 mg/l) of arsenic and manganese on germination, root growth and cell division in root tips of green gram (Vigna radiata.L) were studied. The inhibition of germination and root growth was noticed at higher concentrations of Arsenic and manganese. Arsenic had more toxic effect than manganese on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
3
8
0
Order By: Relevance
“…Roots get inhibited due to direct contact with metals in nutrient media, interfering with normal cellular division and growth pattern. Reduced root growth under As stress might be related to the lower mitotic activity in root meristem that decreased the cell division rate in the apical meristem and inhibited the expansion and elongation of the newly formed cells (Mumthas et al 2010). Similar to the present study, a dose-dependent reduction of root growth (Table 1) was also reported by different investigators for Vigna radiata (Singh et al 2007a, b), Triticum aestivum (Liu et al 2005), Oryza sativa B.…”
Section: Discussionsupporting
confidence: 89%
“…Roots get inhibited due to direct contact with metals in nutrient media, interfering with normal cellular division and growth pattern. Reduced root growth under As stress might be related to the lower mitotic activity in root meristem that decreased the cell division rate in the apical meristem and inhibited the expansion and elongation of the newly formed cells (Mumthas et al 2010). Similar to the present study, a dose-dependent reduction of root growth (Table 1) was also reported by different investigators for Vigna radiata (Singh et al 2007a, b), Triticum aestivum (Liu et al 2005), Oryza sativa B.…”
Section: Discussionsupporting
confidence: 89%
“…Pusa Basant and least obvious in Pusa Jai Kisan. Similar effects of As on seed germination have been observed with wheat, rice, and green gram [29,30]. Seed germination relies almost exclusively on the seed reserves for the supply of metabolites for respiration, as well as other anabolic reactions.…”
Section: Discussionsupporting
confidence: 63%
“…As has been shown to inhibit the lengths of root and shoot in plants [2,28]. The reduction in growth may be due to negative effects of As on cell metabolism, such as energy being channeled into the production of stress-related substances like antioxidases [2,35] and phytochelatins [36,37].Growth inhibition at higher concentrations may be linked with lower mitotic activity in the root meristematic zone or the inhibition of cell enlargement in the elongation zone as a consequence of decreased cellular turgor [30,38]. Root lengthening is controlled by the cell division rate in the apical meristems and by expansion and elongation of the newly formed cells and is considered to be one of the most sensitive endpoints of plant toxicity, where a dose-dependent inhibition of root growth (and of the whole plant), following the administration of relatively high doses of As, has been reported for wheat [26], mung bean [39], Arabidopsis thaliana [40], broad bean [41], and rice [29,42].…”
Section: Discussionmentioning
confidence: 99%
“…Along with high temperature, therefore, reasonably arsenic produces additive PPO activity. The previous study reveals that arsenic accumulation in plant tissues causes several metabolic and physiological disorders (Mumthas et al, 2010), thereby adversely affect growth performance which ultimately leads to reduction of the plant productivity. Arsenic replaces phosphate from ATP to form unstable ADP-arsenic and leads to the disruption of energy metabolism in plant cell.…”
Section: Discussionmentioning
confidence: 99%